The influence of social networks on finding and selecting healthcare professionals - Letícia Miquelitto GASPARONI; Vinícius Neves MARCOS; Cláudio Mendes PANNUTI; Sílvia Maria Morales PEREIRA (Brazilian Oral Research)
Abstract Social networks consist of a group of individuals connected by family, work, or other interests and facilitated by an online structure or platform. They are also a relatively recent and widely used marketing phenomenon that is constantly evolving. The healthcare field includes professions such as social work, biology, biomedicine, physical education, nursing, pharmacy, physiotherapy, speech therapy, medicine, veterinary medicine, nutrition, dentistry, psychology, and occupational therapy. The present study aimed to analyze the influence of social networks in the process of finding and selecting healthcare professionals. The methodology was a survey using a structured questionnaire created on Google Forms. Descriptive research was carried out with non-probabilistic convenience and snowball sampling, followed by quantitative data analysis. A total of 268 participants who signed the informed consent were included in the study. The findings revealed that the most common way to find healthcare professionals is through recommendations from friends/relatives and other professionals, followed by the use of social networks. The majority of participants used social networks to search for healthcare professionals, with Instagram being the most widely used platform. Sponsored advertisements can be an effective way to reach potential new patients. The most valued characteristics in healthcare content creators were reliability, expertise, and the ability to convey messages, with health-related explanations in an easily understandable manner being the preferred type of content. Therefore, this study revealed that social networks can influence the search for and selection of healthcare professionals.